(3hbGjI GdgOGjI aj GdHbGA Ydi JbdjO GdeLJgO HYO ehJgs - (3GdCYQLj, GdMSjfj, GdgGTej, GdfLaj, oRnhjf, CMeO Hf MHjH Hf CMeO, J (B1267(3g`s ((3HNW GdeDdas)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3hHYO agPg LedI hGajI ef GdcdGe hfNHI TGajI aj GdeQGe(B... (3aCbhd(B: (3gd jLhR GdHbGA Ydi JbdjO GdeLJgO HYO ehJg Ce dG(B...s
(3BNQgG (B:s
(3hdG JaYd MJi dG jahJc TjA ef gPg GdeWGdH GdLdjdI hGdMeO ddg ChdG hBNQ(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B109s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3abg GdePGgH GdCNQis